Development of 3D Printable Silver Carp (Hypophthalmichthys molitrix) Surimi Gel with Dynamic High-Pressure Microfluidization-Modified Pea Protein Isolate and Microcrystalline Cellulose - Xiaodan Liu; Qianyu Le; Yi Shi; Ying Yu; Jihao Zeng; Huiyun Chen; Jinhong Wu (Foods)
Sliver carp is a nutritious and abundant species in China, but its low market value stems from its thin meat, small bones and strong odor. Processing it into surimi enhances its economic value, though surimi typically has low gel strength and is prone to deterioration. Recently, three-dimensional (3D) printing has gained attention as an innovative additive manufacturing technique for personalization and process simplification requiring high-performance materials. This study intended to develop an optimized surimi formula for 3D printing with dynamic high-pressure microfluidization (DHPM)-modified pea protein isolate (PPI) and microcrystalline cellulose (MCC). Firstly, the effect of DHPM on PPI properties was evaluated, followed by the optimization of the surimi gel formula (72.093% water content, 3.203% PPI, 1.728% MCC, 1% salt, 1% collagen peptide and 20.976% sliver carp paste) and 3D printing parameters (2000 mm/min at 25 °C with a 1.5 mm nozzle). Rheological comparisons between the optimized surimi, surimi with commercial antifreeze and surimi with only PPI or MCC indicated that the optimized formulation exhibited clearer 3D printing outlines and reduced stickiness due to a higher recovery and lower loss modulus. These results demonstrated that DHPM-treated PPI and MCC enhanced the 3D printability of silver carp surimi gel, providing a new idea for a surimi product and supporting its potential applications in food 3D printing.